Microalgae-bacteria symbiosis enhanced nitrogen removal from wastewater in an inversed fluidized bed bioreactor: performance and microflora - Zheng, Xin; Liu, Ruoting; Li, Kai; Sun, Junhao; Wang, Kanming; Shao, Yuanyuan; Hu, Zhongce; Zhu, Jesse; Pan, Zhiyan; Nakhla, George (Frontiers in Microbiology, 2025)
Conventional wastewater biological nitrogen removal (BNR) processes require a large amount of air and external organic carbon, causing a significant increase in operating costs and potential secondary pollution. Herein, this study investigated the nitrogen removal performance and the underlying mechanisms of a novel simultaneous nitrification and denitrification (SND) coupled with photoautotrophic assimilation system in an inversed fluidized bed bioreactor (IFBBR). Nitrogen removal was achieved through the synergistic interaction of microalgae and bacteria, with microalgae providing O2 for nitrification and microbial biomass decay supplying organic carbon for denitrification. The IFBBR was continuously operated for more than 240 days without aeration and external organic carbon, the total nitrogen (TN) removal efficiency reached over 95%. A novel C-N-O dynamic balance model was constructed, revealing that nitrification and denitrification were the primary pathways for nitrogen removal. The model further quantified the microbial contributions, showing that microalgae generated O2 at a rate of 81.82 mg/L·d, while microbial biomass decay released organic carbon at a rate of 148.66 mg/L·d. Microbial diversity analysis confirmed the majority presence of microalgae (Trebouxiophyceae), nitrifying bacteria (Gordonia and Nitrosomonas) and denitrifying bacteria (Ignavibacterium and Limnobacter). This study successfully achieved enhanced nitrogen removal without the need for aeration or external organic carbon. These advancements provide valuable insights into efficient wastewater nitrogen removal, offering significant benefits in terms of reduced energy consumption, lower operational costs, and decreased CO2 emissions.